(untitled) (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2015)
Glucose is an important commodity for various domestic and industrial applications, ranging from the manufacturing of food and pharmaceuticals to biofuel production. It is therefore imperative to explore novel sources of glucose that are easy to process, cheap and environmentally friendly. In this study, food wastes collected from restaurants and cafeteria within Universiti Malaysia Sarawak (UNIMAS) campus were used as feedstock for glucose production. Several feedstock loadings were investigated (7%, 10%, 20% and 30% w/v) in the enzymatic hydrolysis processes that were carried out at pH 5.0, 100 rpm and 58 Â± 2 Â°C for 24 h using glucoamylase and crude protease preparations. Results showed that substrate concentration of 20% (w/v) in batch hydrolysis experiments has the highest glucose production at 140 g/L, with 46.20% glucose recovery. The highest amount of substrate being hydrolyzed (68.35%) within 20 h was also recorded in the same experimental set. We conclude that substrate concentration or feedstock loading during enzymatic hydrolysis is a very crucial parameter for optimal glucose production and recovery from carbohydrate rich food wastes.